Degradation of organic matters in anaerobic sediments - Lim, Siok Kek; Hanaki, Keisuke; Fude, I.; Shin, Hang-Sik; Lee Foundation, Singapore (Bangkok : Asian Institute of Technology, 1986)
The anaerobic metabolism of organic matters which include the process of fermentation, sulfate reduction and methane production were studied by using sediments from the polluted river. Samples were collected from the lower part of the Chao Phya river. Batch experiment was adopted for the study. Different types and quantities of substrates were introduced into the sediments. Also different quantities of sediments were used in order to examine whether sediment quantities would affect reaction mechanisms. The prepared samples were incubated at 30 °c in the dark. During the incubation period, various parameters such as carbohydrate , sulfate, TOA, etc. were analysed. The results showed that sulfate re- duction was predominant than methanogenesis in the presence of sulfate when acetate was used as the substrate. However, a significant low rate of methanogenesis can be detected in all sediments although rates of sulfate reduction were much higher. On the other hand, in anaerobic freshwater sediment where sulfate concentration was very low, methanogenesis was the major terminal process. The different doses of substrates addition gave the similar patterns of reaction mechanisms while decreased the quantities of sediment used from 30 g to 5 g with 60 ml of river water showed rather slower reaction with less sediment used.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology
Keywords: Sedimentation and deposition